Ecrire chaque expression sous la forme puissance 10

E=10 puissance 7 x 10 puissance 2
F=10 puissance 5 x 10 puissance -9
G= 10 puissance -6 x 10 puissance -6
H= 10 puissance 8 / 10 puissance 3
I= 10 puissance -9 / 10 puissance 2
j= 10 puissance 11 / 10 puissance -5
k=10 puissance -7 / 10 puissance -3
L=10 puissance 3 x 10 puissance -4 / 10 puissance 5 x 10 puissance -7

1

Réponses

2014-01-08T21:34:53+01:00
Bonsoir

E=10 puissance 7 x 10 puissance 2  = 10^9
F=10 puissance 5 x 10 puissance -9 = 10^-4
G= 10 puissance -6 x 10 puissance -6 = 10 ^-12
H= 10 puissance 8 / 10 puissance 3 = 10^5
I= 10 puissance -9 / 10 puissance 2 = 10^-7
j= 10 puissance 11 / 10 puissance -5 = 10^16
k=10 puissance -7 / 10 puissance -3 = 10^-4
L=10 puissance 3 x 10 puissance -4 / 10 puissance 5 x 10 puissance -7

= 10^-1/10^-2 = 10